ENHANCING STUDENTS MOTIVATION IN LEARNING READING COMPREHENSION - HASRIATI NUR (Institut Agama Islam Negeri (IAIN) Bone, 2018)
The objective of this research is to know the students motivated in learning reading comprehension. This research employed descriptive quantitative. The population of this research was the third semester of English Study Program in STAIN Watampone. This research used cluster random sampling. The sample of this research was 25 students. The data were collected by questionnaire. The result of the data showed that the students motivation in learning reading comprehension is 87.14 and it is categorized as strongly motivated. Therefore, it can be stated that motivation is one of the most essential factors that has a direct impact on the enhancing of reading comprehension, but the teachers need to know that the students are motivated differently.